Nonverbal communication of the teacher and motivation for achievement in students of the Educational Institution Fortunato Zora Carvajal, Tacna 2016 - Portocarrero García, Janys Vanessa (2020)
The research object is to determine the correlation between the nonverbal communication of the teacher and the motivation of school achievement of the students of the I. Fortunato Zora Carbajal. It is a basic research, with correlational descriptive design, the sample is composed of 29 teachers and 121 students; We used as an instrument an inventory of 20 items for motivation of achievement and for nonverbal communication a questionnaire with 18 reagents, both instruments were validated and tested for reliability, obtaining 0.74 points and 0.77 points with the alpha method Of cronbach. The results report a 38.02% of teachers with regular level of nonverbal communication, dimension analysis reports for paralanguage 3.2 points, kinetic expression 3.11 points, proxemic expression 2.90 points and chronemic expression 2.68 points. It was also found that 45.5% of the students present a regular level of achievement motivation, dimensional analysis: the task gets 5.86 points, effort 6.55 points, capacity 5.77 points and assessment 5.51 points, due to the scale. The hypothesis was checked with the Pearson correlation coefficient, reporting a r> 0.5 therefore, Ho is rejected and H1 is accepted; It is verified that there is a significant positive linear association at a level of r = 0.908. In conclusion, it is verified that there is a significant correlation between nonverbal communication and motivation of achievement.